Culture and DEIB Movement at International Language Training Organizations in Shanghai and Jakarta - Lingga G. Arieska*; Virienia Puspita; Stephnie Putri Diasti; Radityo Wahyu Senoputro (Universitas Syiah Kuala, 2023)
DEIB (Diversity, Equity, Inclusion, and Belonging) initiative is implemented to tackle equity issues in the organization. The studies on this topic discuss the perception of equity campaigns based on the participants’ cultural backgrounds. This article asserts its point of view from a global language training organization that concentrates its DEIB's mission statement by a committee based in Shanghai, China, alongside a representative committee in Jakarta, Indonesia, where the intercultural backgrounds affected the perception of the movement. The symbolic interactionism point of view of how DEIB ran in these two capitals is made through careful observation and interviews with staff. It suggests that a good campaign within the organization should focus on culturally relevant issues. The campaign format is also highlighted as one thing that must be improved. The sense of ‘belongings’ from each staff in different countries could come from how the information caters to them and how their cultural background defines the issues.